Digital Transformation and Public Service Delivery in Brazil. (12th November 2019) - Filgueiras, Fernando; Flávio, Cireno; Palotti, Pedro
Abstract : This article analyzes the digital transformation process of public services in the Brazilian federal government. Based on a survey with 85 federal organizations, 1, 740 public services are examined according to different factors that explain why a certain public service is digitalized. We discuss the transition from an e‐government to a digital policy, listing the limits related to agent preferences in public policies. The article discusses digital transformation in governments as a process of institutional change in public organizations, taking into account the role of agents, the contexts of choices, and the factors that explain the decision to digitize public services. Abstract : Este artículo analiza el proceso de transformación digital de los servicios públicos en el gobierno federal brasileño. Sobre la base de una encuesta con 85 organizaciones federales, se examinaron 1, 740 servicios públicos en función de diferentes factores que explican por qué se digitaliza un determinado servicio público. Discutimos la transición de un gobierno electrónico a una política pública en materia digital, enumerando los límites relacionados con las preferencias de los agentes en las políticas públicas. El artículo analiza el proceso de transformación digital en los gobiernos como un proceso de cambio institucional de las organizaciones públicas, tomando en cuenta el papel de los agentes, los contextos de elección y los factores que explican la decisión de digitalizar los servicios públicos. Abstract : 本文分析了巴西联邦政府公共服务的数字转型进程。基于一项针对85个联邦组织的调查，根据用于诠释为何公共服务被数字化的不同因素，检验了1, 740项公共服务。我们探讨了电子政府向数字政策的过渡，列出了公共政策中与政府机构偏好相关的限制。本文就政府中数字转型作为公共机构中的制度变化进程进行了探讨，同时考量了政府机构的作用、选择背景、以及用于解释公共服务数字化决策的不同因素。